Exploring drift effects in TCV single-null plasmas with the UEDGE code. (11th August 2017) - Christen, N; Theiler, C; Rognlien, TD; Rensink, ME; Reimerdes, H; Maurizio, R; Labit, B
Abstract: This paper explores the effects of particle drifts across the magnetic field in TCV single-null plasmas using the two-dimensional edge plasma transport code UEDGE. In particular, it aims to reproduce a double-peaked density target profile, a feature which has been observed both at JET and in a TCV forward-field ( ∇ B drift of core ions towards the X -point) discharge. Initial simulations are performed with drift effects turned off. This allows identification of the input parameters that strongly influence the computed steady-state but are not well known from the experiment. Including cross-field drifts self-consistently in the simulations brings computed profiles at the inner target closer to the experiment, with the double peak being reproduced for the density. In agreement with the experiment, simulations of a similar reversed-field shot yield lower n e and higher T e at the inner target, as well as unchanged temperatures at the outer plate. However, several discrepancies remain. In the forward field case, the inner target density peak near the separatrix is much sharper than seen experimentally. Furthermore, simulations show a strong dependence of the outer plate density and of the outer/inner power sharing on toroidal field direction. Experimentally, no such dependencies are observed. In the simulations, the changes of target profiles with field direction are mainly due to E × B drifts in the divertor region. While these simulations highlight the importance of E × B drifts in these TCV plasmas, the remaining differences with the experiment indicate that their role is overestimated in the simulations.